2023
DOI: 10.1017/jns.2023.54
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Dietary Approaches to Stop Hypertension (DASH) diet on the development of preeclampsia and metabolic outcomes in pregnant women with pre-existing diabetes mellitus: a randomised, controlled, single-blind trial

Abstract: Preeclampsia (PE) affects up to five times more women with pre-existing diabetes mellitus (PDM) than women without it. The present study aimed to identify the effect of the DASH diet on PE incidence (primary outcome) and blood pressure, glycated haemoglobin (GH), serum lipids, glutathione peroxidase (GP), C-reactive protein (CRP – secondary outcomes) in pregnant with PDM. This randomised, controlled, single-blind trial studied sixty-eight pregnant women with PDM throughout prenatal care until delivery (18 week… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 45 publications
0
4
0
1
Order By: Relevance
“…Although there were two fetal deaths (one was premature delivery at 34 weeks and 3 days, a newborn with Potter syndrome in the DDG, and the other was born at 36 weeks and 4 days in SDG-of unknown cause), there was no difference in the incidence of maternal complications between the study groups (SDG: 31%, n = 11, v. DDG: 30%, n = 10; p = 0.92),the most frequent being pre-eclampsia that affected 18% of women, without difference between study groups (p = 0.24; Tables in [17]). There was a mean reduction in glycated hemoglobin for both study groups, with no statistical difference between them (p = 0.12-Tables in [17]).…”
Section: Resultsmentioning
confidence: 90%
See 2 more Smart Citations
“…Although there were two fetal deaths (one was premature delivery at 34 weeks and 3 days, a newborn with Potter syndrome in the DDG, and the other was born at 36 weeks and 4 days in SDG-of unknown cause), there was no difference in the incidence of maternal complications between the study groups (SDG: 31%, n = 11, v. DDG: 30%, n = 10; p = 0.92),the most frequent being pre-eclampsia that affected 18% of women, without difference between study groups (p = 0.24; Tables in [17]). There was a mean reduction in glycated hemoglobin for both study groups, with no statistical difference between them (p = 0.12-Tables in [17]).…”
Section: Resultsmentioning
confidence: 90%
“…Regarding diet adherence in both groups, at least 48% of pregnant women showed good adherence to the diet considering all appointments with the nutritionist, and there was no difference between groups at any of the nutritional appointments (p > 0.05-Tables in [17]).…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…The positive effect of DASH nutrition is mainly on anthropometric indices such as body-mass index, but also improvements in blood pressure and glucose levels [53–55]. A small number of studies have reported lowered levels of CRP after initiation of the DASH diet, whilst other report conflicting results (see Table 3 for selected randomized-controlled trials investigating the effect of the DASH diet on inflammatory biomarkers) [56 ▪▪ ,57–59]. From a mechanistic viewpoint, the ani-inflammatory effect of the DASH diet could be mostly attributed to an increased uptake of vegetables as well as fruits, which have been proven to reduce inflammatory burden [60].…”
Section: Targeting Low-grade Inflammation and C-reactive Protein Via ...mentioning
confidence: 99%
“…Çalışmalar Akdeniz diyetine bağlılığın, GDM gelişim riskini azaltabileceğini göstermiştir [12], [13]. Yapılan çalışmalarda, Hipertansiyonu Durdurmaya Yönelik Diyet Yaklaşımları (DASH) diyetinin fetüs üzerindeki yararlı etkilerine ek olarak, bu diyetin GDM'li kadınlar tarafından uzun süreli uygulanması aynı zamanda açlık ve tokluk kan şekerini, serum lipitlerini ve anne kan basıncını azaltarak anne sağlığının iyileştirilmesine de katkıda bulunabileceğini ortaya konulmuştur [14], [15], [16].…”
unclassified